An efficient algorithm for adaptive total variation based image decomposition and restoration - Liu, Xinwu; Huang, Lihong (Zielona Góra: Uniwersytet Zielonogórski)
With the aim to better preserve sharp edges and important structure features in the recovered image, this article researches an improved adaptive total variation regularization and H-1 norm fidelity based strategy for image decomposition and restoration. Computationally, for minimizing the proposed energy functional, we investigate an efficient numerical algorithm-the split Bregman method, and briefly prove its convergence.
Keywords: image decomposition; image restoration; adaptive total variation; H-1 norm; split Bregman method